In-Silico Characterization and Homology Modeling of Catechol 1, 2 dioxygenase Involved in Processing of Catechol - an Intermediate of Aromatic Compound Degradation Pathway (Global Journal of Science Frontier Research, 2015)
Catechol 1, 2 dioxygenase (EC 1.13.11.1) is an enzyme intended to catalyze the degradation of catechol an intermediate of phenolic compound from ortho-mechanisms of the 3-oxoadipate pathway. Catechol 1, 2 dioxygenase plays a key role in the aerobic degradation of aromatic compounds, because it is the substrate for aromatic ring cleavage enzymes and as such it can be the starting point of many peripheral metabolic pathways. So, catechol 1, 2 dioxygenase is deliberated for a solution of environmental pollution occurred by aromatic compounds. In this study, we have focused on the in-silico characterization and homology modeling of catechol 1, 2 dioxygenase. The in silico analysis was performed by various computational tools and programmes. The physicochemical properties of the selected catechol 1, 2 dioxygenase were analyzed by using ExPASy'sProtParam tool and it was found that the molecular weight (M.Wt) ranges around 35000 Da. Isoelectric Points (pI) exhibits acidic nature and aliphatic index infers that 95% catechol 1, 2 dioxygenaseare stable. The negative value of GRAVY indicates that there will be better interaction with water. Motif analysis of the sequences was conducted by using MEME for predicting probable domain of catechol 1, 2-dioxygenase. Homology modeling of catechol 1, 2 dioxygenase taken from Pseudomonas aeruginosa MH38 (AC NO: CDH71767) was performed by I-TASSER. Various bioinformatics programmes and servers like RAMPAGE, PROCHECK and ERRAT were used for analysis and validation of final 3D structures created through homology modeling.
Keywords: catechol 1; 2 dioxygenase; catechol; aromatic compounds; homology modeling